2022
DOI: 10.1097/md.0000000000032216
|View full text |Cite
|
Sign up to set email alerts
|

Fertility problems in men carrying a translocation involved in breakpoints on chromosome 17p13: A retrospective, observational study

Abstract: Male infertility is a multifactorial reproductive disorder. The effect of genetic factors on male infertility has been the focus of research. Although a variety of genetic techniques are applied to male infertility in clinical practice, karyotype analysis remains a powerful and inexpensive technology. Reciprocal chromosomal translocation (RCT) is closely related to male infertility, but the clinical phenotypes of RCT carriers are varied, and the underlying pathological mechanism is unclear. Some studies sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Further research should be done on the exact causes. Previous studies have shown that the breakpoint of translocation disrupts the structure and function of important genes related to [39] Related genes on chromosome breakpoints of this study were summarized in Table 3. The SLC26A8 gene, which is located at chromosome 6p21.31, is associated with human AZS.…”
Section: Discussionmentioning
confidence: 99%
“…Further research should be done on the exact causes. Previous studies have shown that the breakpoint of translocation disrupts the structure and function of important genes related to [39] Related genes on chromosome breakpoints of this study were summarized in Table 3. The SLC26A8 gene, which is located at chromosome 6p21.31, is associated with human AZS.…”
Section: Discussionmentioning
confidence: 99%